HUBUNGAN ANTARA KECERDASAN ADVERSITAS DENGAN TINGKAT STRES PADA PENYALAHGUNA NAPZA DI LEMBAGA PEMASYARAKATAN NARKOTIKA KLAS II A YOGYAKARTA - , AYU MUKHIBATUL FADHILAH; , Dr. dr. Carla R. Marchira, Sp. KJ (K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Nowadays, drug abuse problem is reputed as national threat that need to be considered together. Stress and inability to cope with lifeâs problems are factors that cause a person abusing drug. Drug abuse is a crime that not only handled by imposing criminal penalties, but also the need of medical rehabilitation and social guidance in a special Narcotics Penitentiary. Isolated condition, boredom, and possibility of physical violence are pervasive stressors in prison. People should have adversity intelligence to deal with stress and problems in daily life. Adversity quotient is the ability to solve life problems and difficulties. Purpose : to determine the correlation between adversity quotient and stress level among drug abusers in the Narcotics Penitentiary Class II A Yogyakarta. Method : this research is a quantitative analytical survey method using a crosssectional approach. Research conducted on September untill November 2013, to 62 drug abusers in the narcotics penitentiary of Yogyakarta. The modified Adversity Response Profile questionnaire and stress scale questionnaire. Analysis using Pearson. Research result : adversity quotient level of drug abusers is in moderate level/campers (66,1%). Stress level is also in moderate level (95,2%). Statistic test proved that there is no correlation between adversity quotient and stress level (p value = 0,204, Pearson correlation = 0.164). Conclusion : there is no correlation between adversity quotient and stress level among drug abusers in the Narcotics Penitentiary Class II A Yogyakarta.